2007
DOI: 10.1055/s-2007-984723
|View full text |Cite
|
Sign up to set email alerts
|

Deglutition and Respiration: Development, Coordination, and Practical Implications

Abstract: Temporal coordination of deglutition and respiration is essential for survival because both functions share the pharynx as a common pathway. Disruptions in this interface in young infants may result in dysphagia that may lead to aspiration and injury to the developing lung. Likewise, respiratory problems may contribute to the development of swallowing problems. This article focuses on the coordination between swallowing and breathing in infants and children, aspiration during periods of postnatal lung developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 94 publications
(164 reference statements)
0
41
1
2
Order By: Relevance
“…While cough and wet voice (voice changes) were identified as important clinical markers in both studies, the current authors did not find gag to be significantly associated with OPA on either food/fluid consistency in the present cohort. Other clinical markers reported in the literature to be associated with OPA, such as wheeze, stridor, throat clearing, desaturations or apnoea during feeding, laboured breathing during feeding, or temperatures following oral intake [7,8,17], were also not found to be significantly associated with thin fluid aspiration in the current study. While the present authors did not find any clinical markers significantly associated with OPA on purées, DEMATTEO et al [7] reported that colour changes and abnormal respiration presented a nonsignificant relative risk of 3.0 for solid aspiration.…”
Section: Clinical Markers Associated With Swallowing Dysfunctioncontrasting
confidence: 78%
See 3 more Smart Citations
“…While cough and wet voice (voice changes) were identified as important clinical markers in both studies, the current authors did not find gag to be significantly associated with OPA on either food/fluid consistency in the present cohort. Other clinical markers reported in the literature to be associated with OPA, such as wheeze, stridor, throat clearing, desaturations or apnoea during feeding, laboured breathing during feeding, or temperatures following oral intake [7,8,17], were also not found to be significantly associated with thin fluid aspiration in the current study. While the present authors did not find any clinical markers significantly associated with OPA on purées, DEMATTEO et al [7] reported that colour changes and abnormal respiration presented a nonsignificant relative risk of 3.0 for solid aspiration.…”
Section: Clinical Markers Associated With Swallowing Dysfunctioncontrasting
confidence: 78%
“…Apnoea was defined as a halt in respirations and facial colour change observed visually, with an accompanying oxygen desaturation ,90% Sp,O 2 requiring interruption of the feed at least once per feed for more than one feed, as noted by medical/nursing staff. Clinical markers were chosen from reported presentations of oropharyngeal dysphagia and aspiration from the literature [7,8,10,17].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the causes of dysphagia in pediatric populations are often somewhat different than in adult patients [5]. Table 3 summarizes common causes of dysphagia in pediatric patients [1,5,6,7,8,9,10,11,12,13]. …”
Section: Common Causes Of Dysphagiamentioning
confidence: 99%